CoNiMn magnetic films prepared by magnetic field induced codeposition technology. (3rd July 2017) - Yu, Yundan; Wei, Guoying; Ge, Hongliang; Jiang, Li; Sun, Lixia
ABSTRACT: Magnetic fields vertical to electric fields were applied during electrodeposition process to prepare CoNiMn magnetic thin films. Influences of different magnetic intensities on electrochemistry mechanism, nucleation, surface morphology and magnetic property of CoNiMn films were studied. Magnetohydrodynamics phenomenon caused by Lorentz forces during magnetic electrodeposition process tends to agitate the diffusion layer near cathode. It was found out that, CoNiMn films fabricated by magnetic electrodeposition process belonged to a kind of typical progressive nucleation mechanism. Anomalous codeposition phenomenon of CoNi was affected by magnetic fields. Higher magnetic intensity tended to obtain smooth surface of CoNiMn films with smaller and denser particles. Coercivity and remanence of CoNiMn alloy films increased sharply when magnetic field was induced. Magnetic property of vertical direction was better than parallel direction, which indicated that CoNiMn magnetic film possessed good vertical anisotropy.